Youth Employment in Sierra Leone : Sustainable Livelihood Opportunities in a Post-conflict Setting - Peeters, Pia; Cunningham, Wendy; Acharya, Gayatri; Van Adams, Arvil (World Bank, 2012)
This study focuses on short- and medium-term solutions. It informs the government about the type of programs and policies that could improve the employability of young people, paying special attention to areas in which productivity can be rapidly improved. The report consists of six chapters. Chapter two profiles young people in Sierra Leone. Chapter three examines young people in the labor market, with a focus on the labor supply side of the equation (that is, the skills young people bring to the labor market). Chapter four turns to employers (the demand side of the labor market) to better understand why they do or do not employ young people. Chapter five reviews skill development programs to enhance employability of young people in Sierra Leone and other countries and presents policy options for improving worker skills (supply side) and employer interest (demand side). Chapter six summarizes the lessons from the analysis and concludes with policy and program recommendations.